2019
DOI: 10.1016/j.jtcvs.2018.12.104
|View full text |Cite
|
Sign up to set email alerts
|

Initial report on young cardiothoracic surgeons' first job: From searching to securing and the gaps in between

Abstract: Objective: Recent industry studies have projected a deficit in cardiothoracic surgeons by 2030. Little is known about the difficulties of the job search process after cardiothoracic training. The purpose of this study is to explore the current practices of the first job hunt and contract negotiation for young cardiothoracic surgeons, and to identify the gaps in resources available to applicants.Methods: In October 2017, a 56-question survey was e-mailed to recent (2013-2017) board-certified cardiothoracic surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…(27,28) Furthermore, there remains minimal study in how to overcome racial and gender disparities in physician career progression and pay. (29,30) It is thus understandable that this topic is of such importance to physicians when entering unsupervised practice. A Practice Management Seminar was evaluated in Psychiatry residents that involved talks from a nancial analyst regarding concepts of return on investment and reimbursement policies.…”
Section: Discussionmentioning
confidence: 99%
“…(27,28) Furthermore, there remains minimal study in how to overcome racial and gender disparities in physician career progression and pay. (29,30) It is thus understandable that this topic is of such importance to physicians when entering unsupervised practice. A Practice Management Seminar was evaluated in Psychiatry residents that involved talks from a nancial analyst regarding concepts of return on investment and reimbursement policies.…”
Section: Discussionmentioning
confidence: 99%
“…We recently commented 1 on a study by Sterbling and colleagues, 2 which reported the challenges that residents face when finding and securing a first job in cardiothoracic surgery. In the article, Sterbling and colleagues 2 conclude that ''resources, whether institutional or organizational, are sparse and difficult to tailor to individual needs.''…”
Section: Reply: Transparency Of Job Search Needs Improvementmentioning
confidence: 99%
“…Yet, in a survey concerning the experience of first-job seeking CT surgeons, the results emphasized the limited guidance in the field for those securing first employment, despite the length and rigor of residency. 5 Residents do not feel well-supported in this regard due to a lack of individually tailored resources. With the projected shortage of CT surgeons by 2030, organizations and residency programs should pioneer programs to assist in the hiring process, if not integrate them into the yearly meetings.…”
mentioning
confidence: 99%